Giustizia, responsabilità, singolarità. Riflessi etico-giuridici dell’intelligenza artificiale a partire da Emmanuel Levinas - Pautasso, Sara (Filosofia Morale/Moral Philosophy, 2025)
The rise of predictive justice challenges the ontological foundations of legal decision-making, replacing deliberative reasoning with algorithmic probability. This study interrogates the epistemic limits of AI in law through Emmanuel Levinas’ethics of alterity, arguing that algorithmic systems, by prioritizing efficiency over singularity, risk reinforcing structural injustices. A Levinasian perspective urges a juridical paradigm where technology remains subordinated to the irreducible ethical demand of the Other.